Successful endovascular thrombectomy 90 h after stroke onset. (December 2017) - Gunawardena, Rusiru; Cheung, Andrew; Spira, Paul; He, Jianna; Wenderoth, Jason; Chiu, Albert H.Y.
Highlights: Therapeutic time windows for EVT in treatment of ischemic strokes undergoing evolution with use of advanced imaging. In select patient settings, therapeutic time windows for EVT can be safely extended beyond currently accepted limits. We describe a case of EVT up to 90 h since stroke onset. Abstract: Endovascular thrombectomy (EVT) has extended the conventionally accepted time window of treatment, from 4.5 h (ECASS III trial) for intravenous thrombolysis, to 7.3 h for EVT (HERMES collaboration). More recent evidence suggests EVT times could be extended to 24 h in carefully selected patients (DAWN trial). Some patients present after these time windows with large areas of ischemia but little established infarction on imaging. They represent a major dilemma with much to gain from EVT but at theoretically higher risk of a poor outcome. We present a case of near-complete left M1 occlusion in which EVT achieved reperfusion 90 h 41 min after stroke onset with excellent clinical outcome. Current guidelines on treatment windows for EVT according to HERMES collaboration do not reflect individual patient factors. In appropriate patients delayed EVT may give positive clinical outcomes.